Answer:
- Original Rational number is = 6/13
Explanation:
Let Numerator be : x
Denominator be : x + 7
Now,
- Numerator is increased by 6
- Denominator is decreased by 5
- the new rational number obtained is 3/2
Numerator = x + 6
Denominator = ( x + 7) - 5
According to the question,
![\displaystyle \: \sf \dashrightarrow \: (x + 6)/((x + 7) \: - 5) = \: (3)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/be4xifk3wjivwqk42p2uyz9l0f3feqntgx.png)
![\displaystyle \: \sf \dashrightarrow \: 2(x + 6) \: = 3 \{ \: (x + 7 ) - 5\} \:](https://img.qammunity.org/2022/formulas/mathematics/high-school/97qm033wp2pwtd1db3a4mxjmcuss51q9jg.png)
![\displaystyle \: \sf \dashrightarrow \: 2x \: + 12 \: = \: 3(x + 2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/edvf34fzzullgmsm0qv5gss866tzyi1koo.png)
![\displaystyle \: \sf \dashrightarrow2x + 12 \: = 3x + 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/c9zw86vjld5l1fbqp6sc8tobuzab51vkov.png)
![\displaystyle \: \sf \dashrightarrow \: 2x - 3x \: = \: 6 - 12](https://img.qammunity.org/2022/formulas/mathematics/high-school/tsk48f278pu47uyebf84b916gelyi4y8m3.png)
![\: \: \: \displaystyle \: \sf \dashrightarrow \: - x \: = - 6 \\ \\ \: \: \: \: \: \: \displaystyle \: \bf \dashrightarrow \: x \: = 6](https://img.qammunity.org/2022/formulas/mathematics/high-school/plgiobelespuhnqy8koenlkui6dbde9rsh.png)
Numerator = 6
Denominator = x + 7
= 6 + 7
= 13
Thus ,
![\: \bf { \red{ \underline{\dashrightarrow \: obtained \: rational \: number \: = \: (6)/(13) }}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/vbx3r77c1k91pkhw4un98wazbb64mppsgt.png)
![\pink{\rule{160pt}{5pt}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/pkvn20cv03ur5zl3iwg7ojk6lakh8nqjlu.png)